PEMANFAATAN DAUN KATUK (Sauropus adrogynus) DALAM PEMBUATAN TEH HERBAL DENGAN VARIASI SUHU PENGERINGAN - Wulan Kumala Dewi; Noviar Harun; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to know the effect temperature of drying for aktivity katuk leaf herbal tea. Drying katuk leaf herbal tea used with temperature 40°C, 45°C, 50°C, 55°C for 2 hours. This study used Randomized Block Design (RAK) with 4 treatments and 4 replications to get 16 experimental units. The data obtained were analyzed by analysis of variance (ANOVA). If the test results show F arithmetic greater or equal to F table then tested further with Duncan New Multiple Range Test (DNMRT), at 5% level to know the difference of influence on each treatment. The results showed that moisture content of 6.49-3.87%, ash content of 1.23-1.27% and antioxidant 14.08-56.06μg/ml. The results of the study indicate that for the overall assessment that the panelists rather like to love the leaves produced katuk herbal tea.  Keywords: Leaves katuk, herbal tea and drying.